Cesarean scar pregnancy: A case report with surgical management after initially effective conservative treatment. (2019) - Tsakiridis, Ioannis; Chatzikalogiannis, Ioannis; Mamopoulos, Apostolos; Dagklis, Themistoklis; Tsakmakidis, Georgios; Athanasiadis, Apostolos; Kalogiannidis, Ioannis
Highlights: Cesarean scar pregnancies represent a severe obstetric entity, which is probably associated with the increasing rates of cesarean sections. There is no consensus on the preferred mode of treatment for cesarean scar pregnancies. Even after an initially effective conservative management, surgical management may be needed for the final treatment of cesarean scar pregnancies. Abstract: Introduction: The incidence of cesarean scar pregnancies (CSPs) is increasing, possibly due to higher rates of cesarean sections. We report a case of a CSP with severe bleeding following initial conservative management, that was eventually treated surgically. Presentation of the case: A 33-year old woman with history of one cesarean section presented with abdominal pain and amenorrhea and was diagnosed with CSP. Conservative management with methotrexate was chosen and the treatment was regarded as successful after the expected reduction in serum hCG levels. Four days after the hospital discharge, the patient was readmitted with hemodynamic instability and an emergency laparotomy was performed to remove the remaining trophoblastic tissue. Discussion: A CSP may present as a threatened miscarriage, or remain asymptomatic through the first trimester. Medical treatment may be successful, however a close follow-up is needed even after a reduction in serum hCG levels. Conclusion: We report a case of CSP that, following an initial apparently "successful" treatment with methotrexate, required surgical management due to heavy bleeding.